A geological record of multiple Pleistocene tsunami inundations in an oceanic island: The case of Maio, Cape Verde - Madeira, José (2022)
In the Central Atlantic archipelagos – the Canaries, Cape Verde, Madeira and the Azores – tsunami hazard is often regarded as low, when compared with other extreme wave events such as hurricanes and storms. The geological record of many of these islands, however, suggests that tsunami hazard may be underestimated, notwithstanding being lower than in areas adjacent to subduction zones, such as the margins of the Pacific and Indian oceans. Moreover, tsunamis in oceanic islands are generally triggered by local large-scale volcanic flank collapses, for which little is known about their frequency, making it difficult to estimate the probability of a new occurrence. Part of the problem lies in the fact that tsunami deposits are usually difficult to date, and few islands in the world exhibit evidence for repeated tsunami inundation on a protracted timescale. This study reports on the presence of abundant tsunami deposits (conglomerates and sandstones) on Maio Island (Cape Verde) and discusses their stratigraphy, sedimentological characteristics, probable age and tsunamigenic source. Observations indicate that four distinct inundation events of variable magnitude took place during the Pleistocene. One of the tsunami deposits yielded a high-confidence U/Th age of 78.8 +- 0.9 ka, which overlaps within error with the 73 +- 7 ka age proposed for Fogo volcano’s flank collapse, an event known to have had a significant tsunami impact on nearby Santiago Island. This shows that the Fogo tsunami also impacted Maio, resulting in runups in excess of 60 m above coeval sea-level at ca 120 km from the source. Two older deposits, possibly linked to recurrent flank collapses of the Tope de Coroa volcano in Santo Antão Island, yielded lower-confidence ages of 479 to 390 ka and 360 to 304 ka. A younger deposit (<78 ka) remains undated. In summary, the geological record of Maio exhibits well-preserved evidence of repeated tsunami inundation, reinforcing the notion that tsunami hazard is not so low at volcanic archipelagos featuring prominent and highly-active volcanoes such as in Cape Verde.